Implementation of Population Administrative Service Policy in West Likupang District, North Minahasa Regency - Maykel M. Parengkuan; Sisca Beatrix Kairupan; Laurens L. Bulo (International Journal of Information Technology and Education, 2026)
The study is important because administrative documents are not merely clerical outputs; they constitute legal instruments through which citizens access inheritance rights, banking services, land administration, insurance claims, and other civil entitlements. Using a qualitative descriptive approach, the original thesis gathered data through interviews, observation, and documentation involving subdistrict officials, village-level actors, and community users from mainland and island villages. The article follows the journal format used in the supplied Sammy/F. David model by presenting an abstract, introduction, theoretical framework, method, findings, discussion, conclusion, and references. Findings show that the SKAW service has a formal procedural structure consisting of application registration, population-data and domicile verification, document drafting, authorization, and document delivery. However, implementation remains uneven. The main problems are repeated file returns, incomplete documents, weak preliminary verification at the village level, manual document preparation, dependence on authorized signatories, uneven staff competence, limited public information, weak intergovernmental coordination, inadequate technology, and geographical barriers faced by island communities. Determinant factors include document completeness and data accuracy, human resource capacity, institutional coordination, infrastructure and digital technology, and community access. The article argues that service improvement requires not only administrative compliance but also citizen-oriented service design, integrated village-subdistrict coordination, digital templates and tracking, staff capacity development, and special access mechanisms for island communities.